Secure file sharing with public key infrastructure (PKI) enablement / Noor Azlina Ismail @ Hassan - Ismail @ Hassan, Noor Azlina (2015)
Nowadays, security and privacy is needed in during transferring a file through network especially when transferring an important and confidential document. By using digital certificate that issuance by Certificate Authority with Public Key Infrastructure (PKI) approach for this sytem, people can ensure the security and privacy of exchange file with digital signature through insecure network. The public key and private key cryptographic key pair that is obtained and shared through trusted authority will used to sign and verify the document file. The PKI is used to secure the exam question file during the preparation of exam question at Universiti Teknologi MARA, Jasin, Melaka. This system will used RSA and SHA-256 to produce digital signature because both of the algorithm consist more advantages than other algorithm which is suitable to used to protect document in current insecure network. The result of digital signature that has been produce by the system can be seen in the sign file module. As for digital storage, USB token with authentication mechanism can be used to protect the digital certificate from being stolen by other people as future recommendation.